Sistem Informasi Akuntansi Penjualan Tunai Dan Penerimaan Kas Berbasis Multiuser Pada Toko Harnova Tanggungharjo - Sekar Putri Pertiwi; Febryantahunuji Febryantahunuj; imam Saufik (Pusat Riset dan Inovasi Nasional, 2023)
In the modern and instant era of globalization, companies are required to be able to compete in improving performance and be able to produce appropriate reports. In a trading company, sales are the main activity to generate profit. Good sales and recording procedures and in accordance with company needs can be carried out with a sales accounting system. Sales themselves are divided into two, namely cash sales and credit sales. In this study, the intended sales accounting system is the cash sales accounting system.This research was conducted at the Harnova Tanggungharjo Store, where the Harnova Store is a company engaged in the sale of clothes. Cash sales and cash receipts are very important in an agency, because cash is an important asset. In recording sales and cash receipts, this agency still uses manuals. A computer is a tool that can store data, process data and provide useful information for companies to advance their companies.This study designs a system that can help companies calculate sales and cash receipts. With the cash sales information system and cash receipts, it is expected to be able to carry out procurement, planning and sales supervision very well. besides that it can also produce reports that are precise, accurate and efficient. The software that I use is Microsoft Visual Basic 6.0 with SQL Server 2000 database